STRATEGI PENGEMBANGAN BISNIS MELALUI PENDEKATAN BUSINESS MODEL CANVAS PADA PT PITU KREATIF BERKAH - Zulkarnain Zulkarnain; Mohamad Guruh Saputra; Deli Silvia (Journal Industrial Servicess, 2020)
The location of PT Pitu Kreatif Berkah which was in the printing area causes intense competition because there were many competitors who have competitive quality so that it has an impact on determined the price of the services offered. The purpose of this study was to determine the position of the company and company strategy in accordance with the grand strategy matrix and to make proposals for new business models using the method Business Model Canvas. This study used a SWOT analysis to determine the right business strategies by looking at the strengths, weaknesses, opportunities and threats that PT Pitu Kreatif Berkah has. Analytical Hierarchy Process (AHP) was used to weight obtained strategies to find which strategy has the highest priority based on expert views. Then the business model was used to describe the method Business Model Canvas. The research results obtained 7 strategies based on the SWOT analysis. Based on the results of the weight gave by the experts, that the first alternative strategy was an alternative priority strategy with a weight of 0.320. The alternative strategy was to increase production and establish cooperation with SMEs without reducing the quality and timeliness of the processing process. These strategic priorities are applied to the BMC concept. Based on the priority results that have been applied, there were 6 proposed developments from 9 BMC blocks.